Web-Based Geographic Information System for Hopeful Family Program (HFP) and Non HFP in Handil Bakti Village - Linda Linda; Syafei Karim; Eko Junirianto (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2022)
Handil Bakti Village, Palaran District, Samarinda City is the oldest village in Palaran District, Samarinda City, Handil Bakti Village. The Indonesian government distributes assistance to the lower class community to help ease the burden in daily life. The assistance programs are the Hope Family Program (HFP) and Non HFP. Information and data about the Hope Family Program (HFP) and Non-HFP communities in Handil Bakti Village are very important so that the assistance provided can be right on target and poverty reduction can be achieved. Therefore, it is necessary to have the role of an information system to identify underprivileged communities and poor household data, so that the assistance distributed can be right on the intended target. One of the identification information systems that can be used is the Geographic Information System (GIS). GIS is very efficient in terms of storing, manipulating, analyzing, and displaying geographic data with the help of spatial data and attribute data. From the explanation above, the authors create a system, namely a geographic information system for the Hope Family Program (HFP) and Non HFP data whose purpose is to make it easier for various parties to access information on community data for the Hope Family Program (HFP) and Non HFP anytime anywhere via the internet, because the web can be accessed easily via desktop and mobile devices